Reinforced concrete highway defects and damages in the roadway structures of bridges appearance to be analysis (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2025)
The occurrence of defects is caused by various natural phenomena, the effects of rolling stock, as well as certain shortcomings in the construction technology, construction and operation of the structure.